2008
DOI: 10.1107/s1600536807068304
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl 4-chloro-3-nitrobenzoate

Abstract: Key indicators: single-crystal X-ray study; T = 298 K; mean (C-C) = 0.003 Å; R factor = 0.046; wR factor = 0.130; data-to-parameter ratio = 14.6.In the molecule of the title compound, C 9 H 8 ClNO 4 , an intramolecular C-HÁ Á ÁO hydrogen bond results in the formation of a planar five-membered ring, which is nearly coplanar with the adjacent six-membered ring, the rings being oriented at a dihedral angle of 4.40 (3) . In the crystal structure, intermolecular C-HÁ Á ÁO hydrogen bonds link the molecules. Related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…For related structures, see: Mohd. Maidin, Abdul Rahim, Osman et al (2008); Li et al (2008Li et al ( , 2009. For details of hydrogen-bond motifs, see: Bernstein et al (1995).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…For related structures, see: Mohd. Maidin, Abdul Rahim, Osman et al (2008); Li et al (2008Li et al ( , 2009. For details of hydrogen-bond motifs, see: Bernstein et al (1995).…”
Section: Related Literaturementioning
confidence: 99%
“…The bond lengths (Allen et al, 1987) and angles observed in (I) are within normal ranges and are consistent with other related structures (Mohd. Maidin, Abdul Rahim, Osman et al, 2008;Li et al, 2009;Li et al, 2008). The C1-H1A•••O4 i intermolecular interactions (Table 2) linked the molecules into dimers forming 10-membered rings with R 2 2 (10) motifs (Bernstein et al, 1995).…”
Section: Data Collectionmentioning
confidence: 99%